The Impact of Digital Money on Students' Lifestyle and Financial Management - Dwi Kartika; Yadittiya Laksamana; Ria Melia; Rahmadhani Rahmadhani (CV. Civiliza Publishing, 2026)
The rapid development of digital payment technology has changed how students conduct daily transactions and manage personal spending. This study analyzes the impact of digital money on students' lifestyle and financial management, particularly shopping behavior, payment application preferences, financial recording, and the shift from offline to online shopping. A descriptive quantitative approach was applied. Data were collected through an online questionnaire distributed using Google Forms. From 43 responses received, 40 valid responses were selected after screening according to the research characteristics. The data were analyzed using frequency distribution and percentage analysis, then interpreted with support from technology acceptance, digital payment, and financial literacy literature. The findings show that the respondents were dominated by women (77.5%), the 16-25-year age group (97.5%), and students (92.5%). QRIS was the most frequently used digital money application (45.0%) and remained dominant in the fairly often used category (47.5%). For shopping behavior, neutral and agree responses each reached 37.0%. For financial recording and management, 42.0% of responses were neutral and 41.0% were agree. In the shift from offline to online shopping, 44.5% of responses were agree. These results indicate that digital money offers convenience and efficiency, but its benefits depend on financial awareness, self-control, and the ability to use transaction records for personal financial evaluation.